DEFENCE SPENDING IN SPAIN: A METHODOLOGICAL NOTE (Journal of the Spanish Institute for Strategic Studies, 2013)
This paper analyzes the definition of defence expenditure that is used by various international institutions. The aim is twofold. First to compare these definitions underlining the main differences between them and, secondly, to conduct a comparative study based on their estimates of Spanish defence spending. Finally an analysis of the existing divergences between budgetary data and actual expenditure is performed.